Efeito da guanosina contra danos agudos e crônicos causados por trauma crânio encefálico: uma nova perspectiva envolvendo o sistema purinérgico - Dobrachinski, Fernando (2017)
Traumatic brain injury (TBI) is a multipathology associated to severe physiological changes that result in an unfavorable socioeconomic impact in a worldwide. Its pathophysiology comprises excitotoxicity, mitochondrial dysfunction and inflammatory processes leading to cells death in the central nervous system. Consequently, cognitive changes converge to clinical manifestations, such as behavioral deficits and the appearance of neurodegenerative processes. In experimental models of TBI many promising drugs reported failures when clinically tested, largely because of their effects on a single system. Thus, it is sought to study new therapeutic alternatives such as Guanosine (GUO), an endogenous purinergic nucleoside. At present, attention has been paid to its neuroprotective effects, since it reduces neurotoxic and degenerative events in several experimental models in vivo and in vitro. In this context, the objective of this thesis was to evaluate the possible effects of GUO on the acute and chronic alterations caused by TBI and in a model of excitotoxicity in rodents. The action of purinergic nucleoside was investigated in different experimental models and the results divided into one scientific paper and two manuscripts. The results of article 1 demonstrated the neuroprotective action of GUO against the acute effects observed in the secondary cascade 3h post-trauma. The imbalance in mitochondrial activity and the redox system in TBI model, were reduced by GUO in cerebral structures. At the same time, we can note the effectiveness of GUO in the maintenance of Ca2+ homeostasis modified after TBI. This effect reveals the relationship between the restoration of mitochondrial activity and the maintenance of the glutamatergic system produced by GUO. In manuscript 1, the study focuses on assessing the relationship of behavioral and morphological chronic changes triggered by TBI (for 21 days), as well as the potential action of GUO. Regarding the comorbidities referenced in this experimental model, we observed an increase in the anxiety-like behavior of animals, accompanied by impairments in cognitive function. Its corroborates with the alterations found in the expression of proteins related to the processes of plasticity and synaptic repair in the hippocampus. In this way, hippocampus damage is characterized by an increase of neuron cell death, astrogliosis and reactive microgliosis 21 days after TBI. Chronic treatment with GUO conferred neuroprotection against these parameters, but the A1 adenosine receptor antagonist blocked this effect. In manuscript 2, the study focused on evaluating possible targets of the pharmacological action of GUO in a model of excitotoxicity. Across electrophysiological tools, it can be confirmed the protective effect of GUO against excitotoxicity, through the astrocytic function. In this context, it was found that the homeostasis of calcium (Ca2+) is essential for its activity and this neuroprotection effect is not only dependent on the Ca2+ or potassium (K+) channel activity. Moreover, it was observed that GUO established its protective effect by regulating adenosine levels and modulating P2 (P2Y1) receptors rather than a direct binding with adenosinergic receptors. In this way, this thesis characterized the neuroprotective effect of GUO against acute and chronic damages caused by TBI as well as the possible mechanisms of action involved.